The Molecular Origins of Selectivity in Methanol Decomposition on Pd Nanoparticles - Libuda, Jörg; et al. (Catalysis Letters, 2002)
We have combined multi-molecular beam methods and in-situ time-resolved IR reflection absorption spectroscopy (IRAS) to explore the kinetics of methanol decomposition on a supported Pd model catalyst. The well-shaped Pd nanoparticles are prepared under ultra-high vacuum conditions on a well-ordered alumina film and have previously been characterized with respect to size, density, and morphology. Two competing decomposition pathways are observed: Whereas dehydrogenation to CO represents the dominating reaction channel, C-O bond scission proceeds at much lower rates and leads to the formation of carbon and hydrocarbon species. Using CO as a probe molecule, we show via IRAS spectroscopy that these carbon and hydrocarbon species preferentially block defect sites on the Pd particles such as steps or edges, whereas the (111) facet sites are affected to a lesser extent. Employing quantitative IR Sigma AS and steady-state isotope exchange experiements, the reaction rates for both channels are measured as a function of carbon coverage. It is found that with increasing carbon coverage, the rate of carbon formation drops rapidly, whereas the kinetics of dehydrogenation is hardly affected. These results demonstrate that the rate of C-O bond scission is drastically enhanced at the particle steps and edges, whereas for the dehydrogenation pathway this is not the case.
UnivIS-Import:2015-03-09:Pub.2002.nat.dchph.ppc20.themol
Keywords: Alumina; IR reflection absorption spectroscopy; Methanol; Model catalysts; Molecular beams; Palladium